2013
DOI: 10.1292/jvms.12-0489
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fosfomycin on <i>Escherichia coli</i> Isolated from Bitches with Pyometra

Abstract: ABSTRACT. The aim of this study was to determine the antimicrobial resistance of Escherichia coli isolated from the uteri of bitches with pyometra, and 38 E. coli isolates were used. The antimicrobials used were ampicillin (ABPC), amoxicillin/clavulanic acid, gentamicin, minocycline, cefazolin, levofloxacin (LVFX), trimethoprim-sulfamethoxazole (ST) and fosfomycin (FOM). Resistance to ABPC occurred most frequently, followed by LVFX and ST. Multi-drug resistance, defined as resistance against 3 or more classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
2
5
0
2
Order By: Relevance
“…The highest resistance among the E. coli pyometra isolates in this study was to cephalothin and ampicillin agreeing with Coggan et al [11] but higher than the results reported by Siqueira et al [12] and Inoue et al [13] to ampicillin. Also the results reported to ciprofloxacin, norfloxacin, and gentamicin sensitivity agree with those reported by Siqueira et al [12], Coggan et al [11], and Inoue et al [13]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The highest resistance among the E. coli pyometra isolates in this study was to cephalothin and ampicillin agreeing with Coggan et al [11] but higher than the results reported by Siqueira et al [12] and Inoue et al [13] to ampicillin. Also the results reported to ciprofloxacin, norfloxacin, and gentamicin sensitivity agree with those reported by Siqueira et al [12], Coggan et al [11], and Inoue et al [13]. …”
Section: Discussionsupporting
confidence: 91%
“…The antimicrobial resistances in strains of E. coli from pyometra have been reported by several authors [1113]. The highest resistance among the E. coli pyometra isolates in this study was to cephalothin and ampicillin agreeing with Coggan et al [11] but higher than the results reported by Siqueira et al [12] and Inoue et al [13] to ampicillin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Agostinho (2014) em seu estudo chama a atenção severamente para a estreita relação entre os cães e humanos, e trabalha com a resistência dessa bactéria isolada em piometra, e fatores de risco para o homem (Van Den Bogaard & Stobberingh, 2000;Guardabassi, et al, 2004). A resistência de cepas de E. coli isoladas de piometra já foi relatada por diversos autores (Coggan, et al, 2008;Carlos, et al, 2012;Huber, et al, 2013;Inoue, et al, 2013).…”
Section: Discussionunclassified
“…Foram demonstradas que cepas de E. coli isoladas das fezes como também de piometra, já apresentaram multirresistências em estudos anteriores para cefalotina, ampicilina, ciprofloxacina, norfloxacina e gentamicina, como descrito por Coggan et al (2008), Siqueira et al (2008), Inoue et al (2013), como também foi apresentado nas duas concentrações mais baixas de diluições de Gentrin® no presente estudo.…”
Section: Discussionunclassified